Neoconstitucionalismo e as possibilidades e os limites do ativismo judicial no Brasil contemporâneo - Fernandes, Ricardo Vieira de Carvalho (2010)
This work completes a study cycle whose object was judicial activism. It began in 2009, with the entry of its author in Masters Degree Program in Public Law supported by Prof. Jaci de Assis Law School, of Federal University of Uberlandia. Its apex is the presentation of this study. From the methodological point of view, the research consisted on the analysis of the theoretical literature, based on the deductive method. The two main arguments against a more active behavior of the judiciary are the violation of the principle (to some people, it is a dogma) of the separation of powers and democracy. In order to investigate the first one of them, the research considered the origins of power and its most frequently institutionalized expressions. The study came to the conclusion that power itself cannot be possessed, but exercised, so that it has an intrinsic mobility. Given this premise, the comprehension of that principle was analyzed regarding its evolution since classical theories until contemporary doctrine. The results of the study pointed to its conceptual mobility and fluidity over the centuries, and especially to the fact that the essential core of its expression depends on the settings of power at the moment experienced. Then, the division of powers has been studied considering Brazilian historical and constitutional reality. The partial conclusion extracted from this point was that neither in normality, nor in situations of exception, there was a linear distribution of state power between the established powers in Brazil. The preponderance of the Executive power stood out as well as the growing strength of judiciary, both in its independence and in its political strength. It is important to mention that judiciary is contemporaneously understood, in fact, as a branch of the state. After that, this study stated the conceptual definition of judicialization, judicialization of politics and judicial activism, as well as the presentation of what some theorists have identified as a constitutional crisis. At this point, the analysis of new constitutionalism as a theoretical, ideological and methodological framework for a new paradigm of law emerges as an inevitable element in order to study the proposed object. The post-legal positivism is presented as a philosophical paradigm of the new constitutionalism. Its study is preceded by the presentation of legal positivism in order to demonstrate the major changes of its perspective and some of its excesses. The Constitutional State, the implementation of the Constitution and human dignity as the central value of the system are mentioned. After the general demonstration of the new paradigm, the study investigates the position of Brazilian Judiciary in this perspective, firstly in an overview, then in relation to their legitimacy. Foreign experiences in India, South Africa, United States, Germany, Italy and Spain bring an important contribution to the study of judicial activism in Brazil. Then, in relation to the second main argument against judicial activism (a possible violation of democracy), the research culminates in the legitimate investigation of the possibilities of judicial activism and the presentation of some limits on this activity.